Applications of the Baylis-Hillman reaction in the synthesis of coumarin derivatives - Musa, Musiliyu Ayodele (Rhodes University, Faculty of Science, Department of Chemistry, 2003)
The reaction of specially prepared salicylaldehyde benzyl ethers with the activated alkenes, methyl acrylate or acrylonitrile, in the presence of the catalyst, DABCO, has afforded Baylis-Hillman products, which have been subjected to conjugate addition with either piperidine or benzylamine. Hydrogenolysis of these conjugate addition products in the presence of a palladium-on-carbon catalyst has been shown to afford the corresponding 3-substituted coumarins, while treatment of O-benzylated Baylis-Hillman adducts with HCl or HI afforded the corresponding 3-(halomethyl)coumarins directly, in up to 94%. The 3-(halomethyl)coumarins have also been obtained in excellent yields (up to 98%) and even more conveniently, by treating the unprotected Baylis-Hillman products with HCl in a mixture of AcOH and Acâ‚‚O, obtained from tert-butyl acrylate and various salicylaldehydes. The generality of an established route to the synthesis of coumarins via an intramolecular Baylis-Hillman reaction, involving the use of salicylaldehyde acrylate esters in the presence of DABCO, has also been demonstrated. Reactions between the 3-(halomethyl)coumarins and various nitrogen and carbon nucleophiles have been shown to proceed with a high degree of regioselectivity at the exocyclic allylic centre to afford 3-substituted coumarin products. The electronimpact mass spectra of selected coumarin derivatives have been investigated using high-resolution and B/E linked scan data. Fragmentation pathways have been proposed and fragmentation modes associated with different coumarin-containing analogues have been compared. A series of coumarin-containing analogues of ritonavir (a clinically useful HIV-1 protease inhibitor) have been prepared and characterized. The synthetic approach has involved the coupling of coumarin derivatives with a hydroxyethylene dipeptide isostere to afford ritonavir analogues containing coumarin termini. An interactive docking procedure has been used to explore the docking of ritonavir and a coumarincontaining analogue into the enzyme active site.
Keywords: Coumarins; Heterocyclic compounds -- Derivatives